Composite cathode slurry and use thereof

CN122950413APending Publication Date: 2026-10-20BEIJING CHEHEJIA AUTOMOBILE TECH CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202512017101.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-12-29
Publication Date
2026-10-20

AI Technical Summary

Technical Problem

[0008]本发明针对目前三元材料镍钴锰酸锂(NCM)和磷酸铁锂(LFP)掺混的正极浆料体系存在加工性能和电性能不佳的缺陷和不足,提供一种复合正极浆料,通过特定的NCM\LFP掺混的正极配方协同作用,保证了掺混体系正极浆料的加工性,并改善极片膜片电阻,达成电芯层级较优的动力学性能

Benefits of technology

本发明所提供的复合正极浆料包含磷酸铁锂和三元材料正极活性材料,通过加入含极性基团的改性PVDF作为高分子聚合物粘结剂,可以中和三元材料的碱性,减少正极浆料粘度异常,提升正极片制备的涂覆加工性能,同时结合其他组分改善电性能。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure FT_1
    Figure FT_1
Patent Text Reader

Abstract

This invention provides a composite cathode slurry and its application, relating to the field of lithium battery technology. The composite cathode slurry provided by this invention includes a cathode active material, a conductive agent, a polymer binder, and a dispersant; the cathode active material comprises at least lithium nickel cobalt manganese oxide and lithium iron phosphate; the polymer binder is modified PVDF containing polar groups, wherein the polar groups are selected from any one or more of -COOH, -OH, and -NH2. The composite cathode slurry provided by this invention contains lithium nickel cobalt manganese oxide and lithium iron phosphate cathode active materials. By adding modified PVDF containing polar groups, the alkalinity of the ternary material can be neutralized, improving processing performance and simultaneously enhancing electrical performance. The resulting cathode sheet exhibits low film resistance and good electrical performance, and can be widely used in the preparation of electrochemical devices, significantly improving the electrical performance and long-cycle performance of electrochemical devices.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of lithium battery technology, and in particular to a composite cathode slurry and its application. Background Technology

[0002] Lithium-ion batteries have advantages such as high energy density, high operating voltage, and low self-discharge, and are widely used in power batteries. With the development of new energy vehicles, people are placing higher demands on the energy density, power performance, and cost of lithium batteries.

[0003] The main cathode materials used in lithium-ion batteries mainly include two types: lithium iron phosphate (LiFePO4, LFP) and ternary materials (NCM, Nickel Cobalt Manganese). Each material has its advantages. NCM boasts high discharge capacity and plateau voltage, resulting in high energy density, but its cycle performance and power performance are slightly inferior. LFP offers low cost and good cycle life, but its specific capacity, plateau voltage, and energy density are lower than NCM. Current research aims to develop NCM-LFP blended systems that combine the high specific capacity and high plateau voltage of NCM with the long cycle life of LFP.

[0004] In the design of positive electrode sheets, the positive electrode formulation generally consists of four parts: main material, conductive agent, binder, and dispersant. The proportions and selection of these components are closely related to the main material, and positive electrode formulations with different main materials cannot be simply interchanged. The requirements for positive electrode formulations differ significantly between the two main material systems. NCM powder has a high resistivity, often requiring the addition of a large amount of carbon nanotubes (CNTs) to the positive electrode formulation, increasing the cost. On the other hand, LFP powder has low resistivity and no residual alkali, so CNTs can be omitted from the positive electrode formulation. However, due to its small particle size, LFP is difficult to disperse and requires the addition of an appropriate amount of dispersant.

[0005] Therefore, the research on the development of NCM and LFP blended cathode systems still faces the challenge of how to synergistically improve the processing performance of cathode slurry and the electrical performance of battery through composite cathode formulation design.

[0006] The prior art CN119381420 discloses a lithium manganese iron phosphate composite cathode slurry, comprising the following raw materials: active material, conductive agent, binder, dispersant and solvent; wherein, the active material includes lithium manganese iron phosphate and ternary material, and the mass ratio of lithium manganese iron phosphate to ternary material is (7-9):(3-1); the conductive agent includes conductive carbon black SP (Super P) and multi-walled carbon nanotubes; the binder includes polyvinylidene fluoride (PVDF) binder A with a molecular weight of 600,000-800,000 and PVDF binder B with a molecular weight of 900,000-1,200,000; the dispersant includes a polymer with anchoring groups and a soluble long-chain structure.

[0007] This composite cathode slurry is mainly designed to improve the performance of lithium manganese iron phosphate cathode slurry. The ternary material is only added as a dopant to prevent the agglomeration of small lithium manganese iron phosphate particles. Its addition must be strictly controlled in small quantities because the main material system is different. It cannot truly guide and solve the above-mentioned problems existing in composite cathode slurries of LFP and NCM in any proportion. Summary of the Invention

[0008] This invention addresses the shortcomings and deficiencies of current ternary material lithium nickel cobalt manganese oxide (NCM) and lithium iron phosphate (LFP) blended cathode slurry systems, which suffer from poor processing performance and electrical properties. It provides a composite cathode slurry that, through the synergistic effect of a specific NCM / LFP blended cathode formulation, ensures the processability of the blended cathode slurry system and improves the electrode film resistance, achieving superior kinetic performance at the cell level.

[0009] Another object of the present invention is to provide an application of a composite cathode slurry in the preparation of an electrochemical device.

[0010] Another object of the present invention is to provide a positive electrode sheet.

[0011] Another object of the present invention is to provide a battery cell.

[0012] Another object of the present invention is to provide a battery cell module.

[0013] Another object of the present invention is to provide a battery pack.

[0014] Another object of the present invention is to provide an electrical device.

[0015] In a first aspect, the present invention protects a composite positive electrode slurry, comprising a positive electrode active material, a conductive agent, a polymer binder, and a dispersant; wherein the positive electrode active material comprises at least lithium nickel cobalt manganese oxide (NCM) and lithium iron phosphate (LFP). The polymer binder is a modified PVDF containing polar groups, wherein the polar groups are selected from at least one of -COOH, -OH, and -NH2.

[0016] According to the composite positive electrode slurry protected by the present invention, preferably, the conductive agent includes carbon black and carbon nanotubes, and the mass ratio of carbon black and carbon nanotubes is (65~99):(35~0).

[0017] According to the composite positive electrode slurry protected by the present invention, preferably, the conductive agent includes carbon black and carbon nanotubes, and the mass ratio of carbon black and carbon nanotubes is (70~90):(30~10).

[0018] According to the composite cathode slurry protected by the present invention, preferably, the mass percentage of carbon nanotubes in the composite cathode slurry is a, and the mass percentage of NCM in the composite cathode slurry is b, where a = b × (0.04~0).

[0019] According to the composite positive electrode slurry protected by the present invention, preferably, a = b × (0.005~0.01).

[0020] According to the composite cathode slurry protected by the present invention, preferably, the modified PVDF has a molecular weight of 500,000 to 2,000,000.

[0021] According to the composite cathode slurry protected by the present invention, preferably, the modified PVDF has a molecular weight of 750,000 to 1,500,000.

[0022] According to the composite positive electrode slurry protected by the present invention, preferably, the mass ratio of NCM to LFP in the positive electrode active material is (1~99):(99~1).

[0023] According to the composite positive electrode slurry protected by the present invention, preferably, the mass ratio of NCM to LFP in the positive electrode active material is (1~30):(99~70).

[0024] According to the composite positive electrode slurry protected by the present invention, preferably, the content of the polymer binder is 0.5 wt% to 2.8 wt%.

[0025] According to the composite positive electrode slurry protected by the present invention, preferably, the content of the conductive agent is 0.1 wt% to 2 wt%.

[0026] According to the composite positive electrode slurry protected by the present invention, preferably, the content of the dispersant is 0.01wt%~0.3wt%.

[0027] Secondly, the present invention also specifically protects a method for preparing a composite positive electrode slurry, comprising the following steps: NCM / LFP, carbon black, carbon nanotubes, PVDF binder, and dispersant are mixed in an organic solvent and stirred evenly to prepare a composite cathode slurry.

[0028] Thirdly, the present invention also specifically protects a positive electrode sheet, including a current collector and an active coating disposed on the surface of the current collector, wherein the active coating is made of the composite positive electrode slurry.

[0029] Fourthly, the present invention also specifically protects a battery cell, including the positive electrode plate mentioned in the present invention.

[0030] Fifthly, the present invention also specifically protects a battery cell module, including the positive electrode or battery cell mentioned in the present invention.

[0031] Sixthly, the present invention also specifically protects a battery pack, including the positive electrode sheet or cell or cell module mentioned in the present invention.

[0032] In a seventh aspect, the present invention also specifically protects an electrical device, wherein the electrochemical device includes the positive electrode sheet, cell, cell module, or battery pack mentioned in the present invention.

[0033] Beneficial effects: The composite cathode slurry provided by this invention contains lithium iron phosphate and ternary cathode active materials. By adding modified PVDF containing polar groups as a polymer binder, the alkalinity of the ternary materials can be neutralized, the viscosity abnormality of the cathode slurry can be reduced, and the coating and processing performance of the cathode sheet can be improved. At the same time, it can be combined with other components to improve the electrical performance.

[0034] The positive electrode sheet prepared by the composite positive electrode slurry of the present invention has a low film resistance and good electrical properties. It can be widely used in the preparation of battery cells, battery cell modules, battery packs and electrical devices, significantly improving electrical performance and long cycle performance. Attached Figure Description

[0035] To more clearly illustrate the technical solutions in this invention or the prior art, the drawings used in the description of the embodiments or the prior art will be briefly introduced below. Obviously, the drawings described below are some embodiments of this invention. For those skilled in the art, other drawings can be obtained from these drawings without creative effort.

[0036] Figure 1 The image shows the detection results of the gelation phenomenon in Comparative Example 1. Detailed Implementation

[0037] To make the objectives, technical solutions, and advantages of this invention clearer, the technical solutions of this invention will be clearly and completely described below with reference to the accompanying drawings. Obviously, the described embodiments are only some, not all, of the embodiments of this invention. All other embodiments obtained by those skilled in the art based on the embodiments of this invention without creative effort are within the scope of protection of this invention.

[0038] In a specific embodiment, the present invention provides a composite positive electrode slurry, comprising a positive electrode active material, a conductive agent, a polymer binder, and a dispersant; wherein the positive electrode active material comprises at least lithium nickel cobalt manganese oxide (NCM) and lithium iron phosphate (LFP). The polymer binder is a modified PVDF containing polar groups, wherein the polar groups are selected from at least one of -COOH, -OH, and -NH2.

[0039] It should be noted that: The composite cathode slurry provided by this invention comprises lithium iron phosphate (LFP) and ternary lithium nickel cobalt manganese oxide (NCM) as the active cathode material. The high resistivity of the composite cathode slurry can be improved by adding a conductive agent, and the difficulty in particle dispersion can be addressed by adding a dispersant. In particular, the addition of modified PVDF containing polar groups as a polymer binder in the NCM and LFP composite cathode slurry provides both a binding effect and neutralizes the alkalinity of the ternary material, improving processing performance. Simultaneously, it combines with other components to improve electrical performance, thus simultaneously leveraging the high specific capacity and high plateau voltage advantages of NCM while also possessing the long cycle life advantages of LFP.

[0040] In some specific embodiments, the conductive agent mentioned in this invention may specifically include carbon black and carbon nanotubes, with the mass ratio of carbon black to carbon nanotubes being (65~100):(35~0).

[0041] In some specific embodiments, the conductive agent mentioned in this invention can be carbon black alone, i.e., the mass ratio of carbon black to carbon nanotubes is 100:0. In actual production applications, carbon nanotubes (CNTs) are added to improve the resistivity of NCM, but CNTs are expensive. In the composite cathode slurry provided by this invention, for the scheme using carbon black alone, combined with the improvement of the anti-coagulant properties of specific PVDF, the uniform dispersion of conductive agent and active material can be effectively promoted, effectively improving the processing stability of cathode slurry, while reducing production costs.

[0042] In some specific embodiments, another preferred choice for the conductive agent mentioned in this aspect is a mixed conductive agent of carbon black and carbon nanotubes, wherein the mass content of carbon nanotubes in the mixed conductive agent is preferably controlled to not exceed 35%. Carbon nanotubes have a good effect on improving electrical properties as a conductive agent, but excessive addition will lead to over-addition and entanglement, which will affect the processing performance and electrical performance. Uneven distribution of the conductive agent will result in no significant improvement in electrode resistance, and the addition of excessive carbon nanotubes will increase production costs.

[0043] In some specific embodiments, the mass ratio of carbon black to carbon nanotubes can be further preferably controlled as (70~90):(30~10).

[0044] For example, taking 100 parts by weight of the total conductive agent, the mass of carbon black can be 70 parts, 80 parts, 90 parts, or any other value or range of arbitrary composition, and the mass of carbon nanotubes can be 10 parts, 20 parts, 30 parts, or any other value or range of arbitrary composition.

[0045] In some specific embodiments, in the implementation examples of the conductive agent mentioned in this invention containing carbon nanotubes, it is also preferable to control the correlation between the mass percentage content of carbon nanotubes and the mass percentage content of NCM, wherein the mass percentage content of carbon nanotubes in the composite cathode slurry is a, the mass percentage content of NCM in the composite cathode slurry is b, and a=b×(0.04~0).

[0046] In the above content relationship, in the positive electrode active material slurry containing NCM, the amount of carbon nanotubes added in the conductive agent and the amount of NCM added in the positive electrode active material have a specific balance relationship. By controlling the amount relationship, on the one hand, the resistance can be improved, and on the other hand, the overall processing performance can be improved.

[0047] In some specific embodiments, it is further preferred to control the mass percentage of carbon nanotubes in the composite cathode slurry to be 'a', and the mass percentage of NCM in the composite cathode slurry to be 'b', where a = b × (0.005~0.01). For example, in specific embodiments, the ratio coefficients of a and b can be point values ​​such as 0.005, 0.006, 0.007, 0.008, 0.009, 0.01, or any range of values.

[0048] In some specific embodiments, the molecular weight of the modified PVDF mentioned in this invention is selected from 500,000 to 2,000,000. For example, the molecular weight of PVDF can be selected from point values ​​such as 500,000, 750,000, 1,000,000, 1,250,000, 1,500,000, 1,750,000, and 2,000,000, or any range of values, and more preferably from 750,000 to 1,500,000.

[0049] Choosing the right molecular weight for PVDF can ensure its bonding performance, enabling it to adhere stably to the surface of the current collector. On the other hand, if the molecular weight is too high, it will be difficult to add to the slurry, making the process more difficult and affecting the overall improvement of electrical performance.

[0050] In specific embodiments, the modified PVDF with a specific molecular weight mentioned in this invention can be synthesized, for example, by suspension synthesis. Suspension synthesis can not only obtain PVDF with a higher molecular weight containing polar groups, but also effectively control the purity of the synthesized PVDF product.

[0051] The positive electrode active material in the composite positive electrode slurry mentioned in this invention can be any ratio of NCM and LFP. In some specific embodiments, the mass ratio of NCM to LFP in the positive electrode active material is (1~99):(99~1).

[0052] For example, based on a total mass of 100 parts, the content of NCM can be a point value or any range of 1 part, 5 parts, 8 parts, 10 parts, 20 parts, 30 parts, 40 parts, 50 parts, 60 parts, 70 parts, 80 parts, 90 parts, 99 parts, etc.; the content of LFP can be a point value or any range of 1 part, 5 parts, 8 parts, 10 parts, 20 parts, 30 parts, 40 parts, 50 parts, 60 parts, 70 parts, 80 parts, 90 parts, 99 parts, etc.

[0053] In some specific embodiments, the preferred mass ratio of NCM to LFP mentioned in this invention is (1~30):(99~70).

[0054] The amount of dispersant added in the composite positive electrode slurry mentioned in this invention can refer to the conventional dosage. In some specific embodiments, the content of the dispersant mentioned in this invention can be, for example, 0.01wt%~0.3wt%, such as 0.01 wt%, 0.03 wt%, 0.05 wt%, 0.08 wt%, 0.1 wt%, 0.15 wt%, 0.2 wt%, 0.25 wt%, 0.3 wt%, etc., or any range of values.

[0055] The content of the polymer binder in the composite cathode slurry mentioned in this invention is 0.5wt% to 2.8wt%, for example, it can be a point value of 0.5wt%, 0.8wt%, 1.0wt%, 1.2wt%, 1.5wt%, 1.8wt%, 2.0wt%, 2.5wt%, 2.8wt%, or any range of values.

[0056] The conductive agent content in the composite positive electrode slurry mentioned in this invention is 0.1wt%~2wt%, for example, it can be a point value of 0.1wt%, 0.5wt%, 0.8wt%, 1.0wt%, 1.5wt%, 1.8wt%, 2wt%, or any range of values.

[0057] The dispersant mentioned in this invention is a conventional dispersant in the art, such as polyvinylpyrrolidone, polyacrylic acid, etc.

[0058] In some embodiments provided by the present invention, the composite positive electrode slurry mentioned in the present invention includes positive electrode active material, conductive agent (carbon black and carbon nanotubes), polymer binder, and dispersant; By weight, the positive electrode active material is 95-96 parts, for example 95.2 parts; the conductive agent is 1-2 parts; the polymer binder is 3-4 parts, for example 3.5 parts; and the dispersant is 0.01-0.5 parts, for example 0.3 parts. The mass ratio of NCM to LFP in the positive electrode active material is (1~30):(99~70), for example, it can be 30:70 or 20:80; The mass ratio of carbon black to carbon nanotubes in the conductive agent is (65~99):(35~1), preferably (70~90):(30~10); The polymer binder is a modified PVDF containing polar COOH groups, with a molecular weight of 750,000 to 1,500,000.

[0059] In some preferred embodiments provided by the present invention, the present invention also provides a composite positive electrode slurry comprising a positive electrode active material, a conductive agent (carbon black), a polymer binder, and a dispersant; By weight, the positive electrode active material is 95-96 parts, for example 95.2 parts; the conductive agent is 1-2 parts; the polymer binder is 3-4 parts, for example 3.5 parts; and the dispersant is 0.01-0.5 parts, for example 0.3 parts. The mass ratio of NCM to LFP in the positive electrode active material is (1~30):(99~70), for example, it can be 30:70; The polymer binder is a modified PVDF containing polar COOH groups, with a molecular weight of 750,000 to 1,500,000.

[0060] In a specific embodiment, the present invention also provides a method for preparing a composite positive electrode slurry, comprising the following steps: NCM / LFP, carbon black, carbon nanotubes, PVDF binder, and dispersant are mixed in an organic solvent (e.g., N-methylpyrrolidone) and stirred until homogeneous to prepare a composite cathode slurry.

[0061] In a specific embodiment, the present invention also provides a positive electrode sheet, which includes a current collector and an active coating disposed on the surface of the current collector, wherein the active coating is made of the composite positive electrode slurry provided by the present invention.

[0062] The positive electrode sheet provided by the present invention is prepared by coating the composite positive electrode slurry of the present invention, and has low film resistance and good electrochemical performance.

[0063] In practical applications, the positive electrode mentioned in this invention can be prepared by referring to the following method: Aluminum foil is used as the positive electrode current collector. It is coated, cold-pressed, cut, and slit to prepare the positive electrode sheet.

[0064] In a specific embodiment, the present invention also provides a battery cell, which includes the above-mentioned positive electrode sheet.

[0065] In specific applications, the battery cell mentioned in this invention can be, for example, a lithium-ion battery cell.

[0066] The lithium-ion cell of the present invention can simultaneously leverage the advantages of high specific capacity and high plateau voltage of NCM, while also possessing the long cycle life advantage of LFP.

[0067] The following methods can be used to manufacture lithium-ion battery cells: Preparation of negative electrode Artificial graphite, conductive carbon (SP), sodium carboxymethyl cellulose (CMC-Na), and styrene-butadiene rubber (SBR) are mixed in deionized water and stirred until homogeneous. The negative electrode is prepared by coating, cold pressing, cutting, and slitting copper foil as the negative electrode current collector; Assemble bare cells Stack the positive electrode, separator, negative electrode, and separator in sequence, with the separator positioned between the positive and negative electrodes to provide isolation. Then wind them up and attach finishing tape at the winding point to obtain the bare cell. Preparation of electrolyte In an argon atmosphere, ethylene carbonate / ethyl methyl carbonate (mass ratio: 3:7) was mixed and then lithium hexafluorophosphate (concentration 1.0 mol / L) was added to obtain the electrolyte. Assemble lithium-ion batteries The bare battery cell is placed in an aluminum-plastic film, dried at 100°C, and then injected with the prepared electrolyte. After vacuum sealing, settling, formation, and shaping, the lithium-ion battery cell is prepared.

[0068] In a specific embodiment, the present invention also provides a battery cell module, which is prepared using the positive electrode sheet mentioned in the present invention, or prepared using the battery cell mentioned in the present invention.

[0069] In a specific embodiment, the present invention also provides a battery pack, which is prepared using the positive electrode sheet mentioned in the present invention, or the battery cell mentioned in the present invention, or the battery cell module mentioned in the present invention.

[0070] In a specific embodiment, the present invention also provides an electrical device, wherein the power battery component of the electrical device includes the positive electrode plate mentioned in the present invention, or the battery cell mentioned in the present invention, or the battery cell module mentioned in the present invention, or the battery pack mentioned in the present invention.

[0071] In the following embodiments and comparative examples of the present invention, the modified polar group of the modified PVDF is -COOH, and the molecular weight is 700,000 to 1,500,000.

[0072] The preparation method can be referred to as follows: Reaction system configuration: Add deionized water (continuous phase), dispersant (such as polyvinyl alcohol (PVA, 0.1~0.5wt%)), 1,1-vinylidene fluoride (VDF, 2~4:1 water / monomer mass ratio), acrylic acid monomer (1~5wt%), and oil-soluble initiator 2,2'-azobisisobutyronitrile (AIBN, 0.05~0.2wt%) to the high-pressure reactor.

[0073] Polymerization reaction: Seal the reactor, heat to 60~90℃, introduce nitrogen or VDF to maintain pressure of 2.0~5.0MPa, stir at 200~500rpm, react for 4~8 hours, monitor the solid content by sampling (usually terminate the reaction when it reaches 30%~40%).

[0074] Post-processing: After the reaction is complete, the suspension is filtered, washed and dried to finally obtain the -COOH modified PVDF powder product.

[0075] Example 1 This embodiment provides a composite positive electrode slurry, comprising a positive electrode active material, a conductive agent (carbon black and carbon nanotubes), a polymer binder, and a dispersant; The mass ratio of the positive electrode active material, carbon black, carbon nanotubes, polymer binder, and dispersant is 95.2:0.8:0.2:3.5:0.3. The positive electrode active material is a mixture of NCM and LFP in a mass ratio of 3:7; The polymer binder is modified PVDF containing polar groups; The mass ratio of carbon black to carbon nanotubes in the conductive agent is 8:2; The dispersant is polyacrylic acid.

[0076] This embodiment also provides a method for preparing the above-mentioned composite cathode slurry, specifically as follows: NCM / LFP, carbon black, carbon nanotubes, PVDF binder, and dispersant were mixed in an organic solvent, N-methylpyrrolidone, and stirred until homogeneous to prepare a composite cathode slurry.

[0077] Example 2 A composite positive electrode slurry includes a positive electrode active material, a conductive agent, a polymer binder, and a dispersant. The difference from Example 1 is that the mass ratio of carbon black to carbon nanotubes in the conductive agent is 6:4.

[0078] Example 3 A composite positive electrode slurry includes a positive electrode active material, a conductive agent, a polymer binder, and a dispersant. The difference from Example 1 is that the mass ratio of carbon black to carbon nanotubes in the conductive agent is 2:8.

[0079] Example 4 A composite positive electrode slurry includes a positive electrode active material, a conductive agent, a polymer binder, and a dispersant. The difference from Example 1 is that the conductive agent is carbon black.

[0080] Example 5 A composite positive electrode slurry includes a positive electrode active material, a conductive agent, a polymer binder, and a dispersant, which is basically the same as in Example 1, except that the positive electrode active material is a mixture of NCM and LFP in a mass ratio of 20:80.

[0081] Comparative Example 1 This comparative example provides a conventional NCM formulation in which NCM is replaced with a mixture of NCM and LFP in a mass ratio of 3:7.

[0082] The difference from Example 1 is that it does not contain a dispersant, and the mass ratio of the positive electrode slurry: NCM / LFP=3:7, carbon black, carbon nanotubes, and binder PVDF is 95.2:1:0.6:3.2.

[0083] Comparative Example 2 This comparative example provides a composite cathode slurry, which is basically the same as that in Example 1, except that the binder PVDF is unmodified PVDF with a molecular weight of 750,000 to 1,500,000.

[0084] Application examples The positive electrode slurries of the above embodiments and comparative examples were prepared into corresponding positive electrode sheets and lithium-ion cells according to the following method, and their performance was tested.

[0085] Preparation method of positive electrode sheet: Aluminum foil is used as the positive electrode current collector. It is coated, cold-pressed, cut, and slit to prepare the positive electrode sheet.

[0086] The fabrication of lithium-ion battery cells: Preparation of the negative electrode: Artificial graphite, conductive carbon (SP), CMC-Na, and SBR are mixed in deionized water at a weight ratio of 96:0.5:1.5:2 and stirred until homogeneous; The negative electrode is prepared by coating, cold pressing, cutting, and slitting copper foil as the negative electrode current collector; Assemble the bare cell: Stack the positive electrode, separator, negative electrode, and separator in sequence, with the separator in the middle of the positive and negative electrodes to provide isolation. Then wind it up and attach tape to the winding point to obtain the bare cell. Preparation of electrolyte: In an argon atmosphere, ethylene carbonate / ethyl methyl carbonate (3:7) was mixed and lithium hexafluorophosphate was added. The concentration of lithium hexafluorophosphate was 1.0 mol / L to obtain the electrolyte. Assembling lithium-ion batteries: The bare cells are placed in an aluminum-plastic film, dried at 100°C, and then injected with the prepared electrolyte. After vacuum sealing, settling, formation, and shaping, the lithium-ion cells are prepared.

[0087] Cathode slurry viscosity test: Take 200ml of fresh slurry and place it in a beaker. Measure the initial viscosity, let it stand and start timing. Test the slurry viscosity every 2-5 hours and record the results until 24 hours.

[0088] Electrode film resistance test: Take the cold-pressed positive electrode sheet and cut it into 50mm*50mm squares, ensuring the surface is flat and undamaged. Then use a film resistance meter (such as PRCD1100 or CRM-01) to measure the corresponding 154.025mm. 2 The resistance value was measured three times and the average value was taken.

[0089] Lithium-ion battery cell DCR (Direct Current Resistance) performance test: Test process: (1) Let stand at 25℃ for 60 minutes; (2) Charge at 1C constant current to 4.25V at 25℃, and charge at 0.05C constant voltage; (3) Let stand at 25℃ for 5 minutes; (4) Discharge at 25℃ with a constant current of 1C until 50% SOC is reached; (5) Let it stand at 25℃ for 60 minutes and record the final voltage U1; (6) Discharge at 4C constant current for 10s at 25℃, record the end voltage U2, DCR=(U2-U1) / 4C.

[0090] The specific test results are shown in Table 1 below.

[0091] Table 1 Serial Number Carbon black to carbon nanotube ratio Viscosity of positive electrode slurry after standing for 24 hours Diaphragm resistance / mΩ DCR / mΩ Example 1 8:2 15780 266.0 12.18 Example 2 6:4 26700 229.7 12.02 Example 3 2:8 30020 230.1 12.05 Example 4 \ 12900 443.7 14.62 Example 5 12300 216.6 11.98 Comparative Example 1 \ 100000+ 295.5 13.39 Comparative Example 2 \ 80000+ 455.1 14.23 Based on the data in Table 1 above, it can be seen that the LFP / NCM blending system formulation requires the simultaneous addition of conductive agents, modified PVDF, and dispersants to ensure that the slurry can be processed normally while having low impedance. It not only has low static diaphragm resistance but also low cell system DCR resistance.

[0092] As can be seen from Examples 2 and 3, when the conductive agent is a mixture of carbon black and carbon nanotubes, increasing the proportion of carbon nanotubes can improve the electrical performance to a certain extent, but it has an adverse effect on the processing performance of the cathode slurry. When the proportion of carbon nanotubes added to the conductive agent is greater than 35%, such as in Examples 2 and 3, the viscosity of the cathode slurry shows a significant increasing trend after 24 hours. Further increasing the amount of carbon nanotubes has limited effect on improving the overall electrical performance and increases production costs.

[0093] The positive electrode slurry in Example 4 exhibited good viscosity stability after 24 hours, indicating that the polymer binder of this invention can effectively improve the processing stability of the positive electrode slurry. Its electrical properties, due to the absence of added carbon nanotubes, are not significantly improved compared to other examples, but still well meet the electrical performance requirements for the use of the positive electrode slurry.

[0094] In Comparative Example 1 (conventional NCM formulation, without dispersant) and Comparative Example 2 (without modified PVDF), the cathode slurry of the blended system exhibited significant slurry gelation problems, preventing subsequent coating and other processes from proceeding normally (only a small number of cathode sheets could be produced before the slurry severely gelled). Their viscosity rebound curves are as follows: Figure 1 In Comparative Example 1, the NCM system cathode formulation used a large amount of carbon nanotubes, which combined with the carbon coating on the LFP surface, causing PVDF long chains to become entangled, resulting in a rapid increase in slurry viscosity. In Comparative Example 2, conventional unmodified PVDF was used as a binder, which obviously could not improve the processing stability of the cathode slurry. The viscosity of the cathode slurry increased sharply after 24 hours, and the slurry gelled.

[0095] The battery cell prepared using the composite cathode slurry provided by this invention not only exhibits the high specific capacity and high plateau voltage advantages of NCM, but also possesses the long cycle life advantages of LFP. This is specifically demonstrated by the test results shown in Table 2 below: Table 2 Experimental group Capacity (mAh / g) Voltage plateau (V) High-temperature cycling (600 cycles) Example 1 165.8 3.39 87.6% Example 2 166.1 3.39 86.8% Example 3 166.2 3.39 88.2% Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, and not to limit them; although the present invention has been described in detail with reference to the foregoing embodiments, those skilled in the art should understand that modifications can still be made to the technical solutions described in the foregoing embodiments, or equivalent substitutions can be made to some of the technical features; and these modifications or substitutions do not cause the essence of the corresponding technical solutions to deviate from the spirit and scope of the technical solutions of the embodiments of the present invention.

Claims

1. A composite positive electrode slurry, characterized in that, Including positive electrode active materials, conductive agents, polymer binders, and dispersants; The positive electrode active material comprises at least lithium nickel cobalt manganese oxide and lithium iron phosphate; The polymer binder is a modified PVDF containing polar groups, wherein the polar groups are selected from at least one of -COOH, -OH, and -NH2.

2. The composite positive electrode slurry according to claim 1, characterized in that, The conductive agent includes carbon black and carbon nanotubes, and the mass ratio of carbon black to carbon nanotubes is (65~99):(35~0).

3. The composite positive electrode slurry according to claim 2, characterized in that, The mass ratio of carbon black to carbon nanotubes is (70~90):(30~10).

4. The composite positive electrode slurry according to claim 2 or 3, characterized in that, The mass percentage content of carbon nanotubes in the composite cathode slurry is a, and the mass percentage content of lithium nickel cobalt manganese oxide in the composite cathode slurry is b, where a = b × (0~0.04).

5. The composite positive electrode slurry according to claim 4, characterized in that, a = b × (0.005~0.01).

6. The composite positive electrode slurry according to any one of claims 1 to 5, characterized in that, The modified PVDF has a weight-average molecular weight of 500,000 to 2,000,000.

7. The composite cathode slurry according to any one of claims 1 to 5, characterized in that, The mass ratio of lithium nickel cobalt manganese oxide to lithium iron phosphate in the positive electrode active material is (1~99):(99~1). And / or, the content of the polymer binder is 0.5 wt% to 2.8 wt%; And / or, the content of the conductive agent is 0.1 wt% to 2 wt%; And / or, the content of the dispersant is 0.01wt%~0.3wt%.

8. A positive electrode sheet, characterized in that, The present invention includes a current collector and an active coating disposed on the surface of the current collector, wherein the active coating is made of the composite positive electrode slurry according to any one of claims 1 to 7.

9. A battery cell, characterized in that, Includes the positive electrode sheet as described in claim 8.

10. A battery cell module, characterized in that, It includes the positive electrode sheet as described in claim 8 or the battery cell as described in claim 9.

11. A battery pack, characterized in that, It includes the positive electrode sheet of claim 8, the battery cell of claim 9, or the battery cell module of claim 10.

12. An electrical appliance, characterized in that, The electrical device includes the positive electrode sheet of claim 8, the battery cell of claim 9, the battery cell module of claim 10, or the battery pack of claim 11.